Fission Xenon Dating - Teitsma, Albert (My University, 1975)
A new dating method has been developed which uses fission product xenon in a manner similar to radiogenic argon in the 40Ar - 39Ar method. Measurable quantities of spontaneous fission xenon accumulate with time in rocks and minerals containing approximately 1 ppm or more of uranium as a result of the spontaneous fission of 238u. In the past, attempts have been made to date this type of sample by measuring the absolute amount of fission product xenon and the uranium content. In the new method a sample is irradiated in a thermal neutron flux to implant xenon from the neutron induced fission of 235u in amounts proportional to the uranium content. After a short cooling period (before radioactive 133xe has decayed) the sample is placed in a high vacuum system and the xenon is released by heating in a series of temperature steps. For each step the isotopic composition of the xenon is measured using a high sensitivity mass spectrameter and the ratio of spontaneous fission xenon to neutron fission xenon is calculated. Fission xenon ages for all steps are then calculated from the spontaneous to neutron fission xenon ratios and the measured integrated neutron flux.
The method has several advantages over the conventional U - Xe technique. {a) The measurement of isotope ratios is inherently more precise than the measurement of absolute quantities. (b) Whereas the conventional U - Xe technique measures the sample date only once, the method described in this thesis measures the sample date several times. (c) If a geological disturbance has caused loss of fission xenon a valid date can still be obtained using the low mobility xenon released at high temperatures. (d) In some samples disturbed dates as well as initial formation dates can be measured.
The method was developed and evaluated by a series of experiments which dated four zircon samples, one sphene sample, and a carbonatite sample. The zircon and sphene samples had been dated in other laboratories by the conventional u - Th - Pb and Rb - Sr methods. Fission xenon dating of these samples provided valuable new geochronological information. The experiments also showed that in addition to the advantages mentioned, the new method appears to be better able to see past metamorphic events than other methods.
Keywords: fission; xenon; dating method; spontaneous fission